Variable expression of hepatic genes in different liver tumor cell lines: conclusions for drug testing - Wisniewska, Monika Joanna; Wencel, Agnieszka; Jakubowska, Malgorzata; Motyl, Joanna Agata; Dudek, Krzysztof; Burzynska, Beata; Pijanowska, Dorota Genowefa; Pluta, Krzysztof Dariusz (Frontiers in Cell and Developmental Biology, 2025)
IntroductionDrug discovery and development is a complex, multi-stage process that often spans over a decade and involves high costs and low success rates. Preclinical testing, particularly the assessment of drug-induced liver injury, plays a crucial role in identifying safe and effective therapeutics before clinical trials. In vitro models based on hepatic cell lines are commonly used to study hepatotoxicity, yet their physiological relevance varies significantly. This study aimed to compare the expression of key liver-specific genes and proteins in four widely used hepatic cancer cell lines—HepG2, C3A, SNU449, and SNU475—with those in primary human hepatocytes.MethodsUsing RT-qPCR, protein analysis and metabolic tests, we assessed the ability of these cell lines to perform liver-specific functions, especially drug metabolism.ResultsWe found significant differences in liver-related gene expression and metabolic profiles among tested cell lines, especially the most striking differences were found between tumor cells of divergent origin: hepatoblastomas and hepatocellular carcinomas.DiscussionOur findings emphasize the importance of careful selection and validation of in vitro models in hepatotoxicity testing, as significant differences exist in their gene expression profiles and functional characteristics.